Product involvement, WOM and eWOM in the fast food industry: A young adult perspective in an emerging African economy - Aobakwe Ledikwe (Taylor & Francis Group, 2020)
This study investigates the relationship between product involvement, WOM, and eWOM in the fast food industry between two sub-groups of young adult consumers in South Africa. A quantitative design was followed, with primary data (n = 201) gathered from respondents using a self-administered questionnaire. The results suggest that product involvement exerts a positive and significant influence on WOM and eWOM in the case of both young adult sub-groups. There is also no difference in the perceptions of the two sub-groups of young adults concerning product involvement, WOM, and eWOM. Product involvement is found to play an important role in spreading WOM and eWOM in the fast food industry, and is proposed as an important focus area for managers.